2008
DOI: 10.1590/s0103-863x2008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Enfrentamento de desastres naturais: o uso de um coping coletivo

Abstract: Resumo: Os desastres naturais estão, atualmente, entre os mais comuns tipos de trauma. O impacto sofrido pelos indivíduos e pela comunidade atingida gera inúmeras respostas emocionais, tornando imperativa a mobilização de esforços para lidar com o evento. Esses são entendidos como estratégias de coping utilizadas para adaptar-se a situações estressoras. Muitos modelos e classificações foram propostos para explicar este conceito, entretanto a maioria permanece com uma percepção individual do processo. O modelo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(11 reference statements)
0
1
0
3
Order By: Relevance
“…In this case, it is demonstrated that the intensity of trauma as an individual response experienced to the impact of the earthquake has a greater effect on the subsequent perception of social well-being through the processes of social sharing of emotions and communal appraisal. Although such processes have been specifically identified as collective coping strategies ( Krum and Bandeira, 2008 ; Páez et al, 2013 ; Palacios and Barrios, 2013 ; Villagrán et al, 2014 ; Wlodarczyk et al, 2016a , b ), it is proposed that they acquire relevance in different post-disaster phases and not only as a set of strategies involving different adaptive and maladaptive responses. On the contrary, according to the results of the multiple mediation model, the social expression of emotions and the communal appraisal would form a route so that the individual reactions could be projected later on in a social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is demonstrated that the intensity of trauma as an individual response experienced to the impact of the earthquake has a greater effect on the subsequent perception of social well-being through the processes of social sharing of emotions and communal appraisal. Although such processes have been specifically identified as collective coping strategies ( Krum and Bandeira, 2008 ; Páez et al, 2013 ; Palacios and Barrios, 2013 ; Villagrán et al, 2014 ; Wlodarczyk et al, 2016a , b ), it is proposed that they acquire relevance in different post-disaster phases and not only as a set of strategies involving different adaptive and maladaptive responses. On the contrary, according to the results of the multiple mediation model, the social expression of emotions and the communal appraisal would form a route so that the individual reactions could be projected later on in a social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Neste sentido, Krum (2007) levanta a importância de identificar as estratégias de coping utilizadas no enfrentamento do estresse decorrente da vivência de um desastre, investigando qual o impacto dessas estratégias sobre as respostas que são dadas pelo indivíduo diante do desastre, propondo reflexões acerca da prevenção em futuros desastres (Krum & Bandeira, 2008).…”
Section: Atuações No Pré-desastreunclassified
“…Entre os autores que preferem instrumentos quantitativos estão Coêlho, Adair e Moccelin (2004 citados por Krum & Bandeira, 2008), que utilizaram três instrumentos: um para medição da ansiedade (STAI), um para investigação do sofrimento emocional (SRQ-20) e um terceiro para verificação da incidência de estresse pós-traumático (TSQ). Para diagnosticar o estresse pós-traumático, Kohn et al (2005) Kessler et al (2006), em pesquisa com os sobreviventes do furacão Katrina, utilizaram a escala K6 para rastrear doenças mentais e ideação suicida, depois de terem feito uma investigação quanto a outras condições médicas, psiquiátricas e psicossociais por meio do questionário NCS-R (National Comorbidity Survey Replication -NCS-R).…”
Section: Atuações Durante O Desastreunclassified
“…No cenário acadêmico referente a estudos em Psicologia, constata-se o aumento no número de estudos que versam sobre o impacto social e individual dos desastres nas populações atingidas (Bobato & Teodoro, 2010;Krum & Bandeira, 2008). Assim, é crescente a discussão em torno das possibilidades de intervenção em catástrofes, delimitando um campo promissor de atuação da Psicologia das Emergências (Carvalho & Borges, 2009;Steinman et al, 2011).…”
Section: Introductionunclassified